Investigation of genotoxic and antigenotoxic activities of Melampodium divaricatum in Salmonella typhimurium - Nogueira, MEI; Passoni, M. H.; Biso, F. I.; Longo, M. D.; Cardoso, CRP; dos Santos, L. C.; Varanda, Eliana Aparecida [UNESP] (Elsevier B.V., 2006)
Melcanpodium divaricatian is a member of the Asteraccae and in Brazil is known as false-calendula, its flowers being used in anti-inflammatory preparations, substituting the true calendula or marigold (Calendula officinalis L.). The flower extract was investigated for mutagenic and antimutagenic effect in the Sahnonella/microsome assay. The tested extract was not mutagenic in the strains TA100, TA98, TA97a and TA102 and decreased the mutagenicity of aflatoxin B1, benzo(a)pyrene and daunomycin. Chlorophyll and triterpenes were detected in the extract, and they might have contributed to the observed effect. Our data suggest that these medicinal plants possess cancer chemopreventive properties. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Salmonella typhimurium; antimutagenic activity; Melampodium divarication; triterpenes